A Mini Zinc-Finger Protein (MIF) from Gerbera hybrida Activates the GASA Protein Family Gene, GEG, to Inhibit Ray Petal Elongation - Han, Meixiang; Jin, Xuefeng; Yao, Wei; Kong, Lingjie; Huang, Gan; Tao, Yujin; Li, Lingfei; Wang, Xiaojing; Wang, Yaqin (Frontiers in Plant Science, 2017)
Petal appearance is an important horticultural trail that is generally used to evaluate the ornamental value of plants. However, knowledge of the molecular regulation of petal growth is mostly derived from analyses of Arabidopsis thaliana, and relatively little is known about this process in ornamental plants. Previously, GEG (Gerbera hybrida homolog of the gibberellin [GA]–stimulated transcript 1 [GAST1] from tomato), a gene from the GA stimulated Arabidopsis (GASA) family, was reported to be an inhibitor of ray petal growth in the ornamental species, Gerbera hybrida. To explore the molecular regulatory mechanism of GEG in petal growth inhibition, a mini zinc-finger protein (MIF) was identified using yeast one-hybrid (Y1H) screen. The direct binding of GhMIF to the GEG promoter was verified by using an electrophoretic mobility shift assay and a dual-luciferase assay. A yeast two-hybrid (Y2H) revealed that GhMIF acts as a transcriptional activator. Transient transformation assay indicated that GhMIF is involved in inhibiting ray petal elongation by activating the expression of GEG. Spatiotemporal expression analyses and hormone treatment assay showed that the expression of GhMIF and GEG is coordinated during petal development. Taken together, these results suggest that GhMIF acts as a direct transcriptional activator of GEG, a gene from the GASA protein family to regulate the petal elongation.